Pengaruh Word of Mouth Promotion dan Service Excellent terhadap Keputusan Nasabah Memilih Giro BTN di Bank BTN Kantor Cabang Bandung Timur - Nisa, Haifa Ainun; Huda, Badriyatul (Ma'soem University, 2024)
Based on the observation results, that the background of this research is that there has been a decrease in the number of current account customers in the last two years, this is due to poor word of mouth promotion and also service excellent that does not meet customer expectations which can affect customer confidence in taking decision. This study aims to determine the effect of word of mouth promotion and excellent service on customers' decisions to choose current account products partially or simultaneously at bank BTN Kantor Cabang Bandung Timur. The object of research in this thesis is BTN Giro customers at bank BTN Kantor Cabang Bandung Timur. The type of research is associative quantitative with primary data types and uses data collection techniques in the form of interviews, lists of statements (questionnaire), observation and literature study. While the sampling technique is non-probability sampling with purposive sampling. The population is all Current Account customers at the bank BTN Kantor Cabang Bandung Timur, totaling 838 people with a sample of 89 people. The results showed that there was a significant effect of word of mouth promotion on the decisions of BTN Giro customers at the BTN bank East Bandung Branch Office of 33.7% where the value of tcount>ttable (6.646>1.662), there was a significant influence of service excellent on customer decisions BTN demand deposits amounted to 40.3% where the value of thitun> ttable (7.656> 1.662), and simultaneously there is a significant influence between word of mouth promotion and service excellent on customer decisions choosing current account products at bank BTN East Bandung Branch Office of 52% with F test results Fcount <Ftable (46.62).